The dynamics of the construction sector in Colombia, a review from its indicators - Sarmiento-Rojas, Jorge Andrés; Universidad Pedagógica y Tecnológica de Colombia; Rueda-Varón, Milton Januario; Universidad EAN; Rincón-González, César Hernando ; Universidad EAN (UPTC Editorial, 2021)
The construction sector plays a leading role in all of the world’s economies, especially in countries in development, because the building of infrastructure is essential for the progress of modern societies. However, the sector experiences are much more pronounced periods of activity than the average economic and is susceptible to variations in international markets. In addition, it is considered one of the main indicators, due to the influence it has on the variations in the economy’s cycle. Therefore, the present research exposes a detailed and explanatory manner of the behavior in the construction sector as a representation of the economic dynamics in Colombia, through the evaluation that characterizes its indicators, the relationship with the economic effects in conjunctural periods and the identification of the main factors that represent the dynamics of construction. Consequently, the evaluation of these complex correlations allowed to constitute orientations in the identification of variables towards the possible adoption of practices and processes, by means of statistical tools for multivariate data management. Likewise, it is possible to foresee future scenarios in the external changes, in order to minimize the impact on the dynamics of the construction sector, projected to the economic behavior of Colombia.